1997
DOI: 10.1108/09649429710182332
|View full text |Cite
|
Sign up to set email alerts
|

Career progression in accountancy ‐ the role of personal and situational factors

Abstract: Examines the personal and situational factors that determine career progression for women in the accountancy profession within the context of the Big Six firms in Scotland from data generated by a postal questionnaire focusing specifically on both male and female senior managers within these firms. The results relating to person-centred data indicate that the most common aspiration of the senior managers relates to the attainment of partnership status. Motherhood appears to modify career expectations and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
(31 reference statements)
2
30
0
1
Order By: Relevance
“…In the occupational domain, gender ideologies were found to be related to women's employment (Crompton & Harris, 1997), job attitudes (Gray, 1989a;Jones & McNamara, 1991), organizational commitment (Gray, 1989b) and career advancement (Gammie & Gammie, 1997). In the marital domain, studies have found associations between gender ideologies and J O B I N S E C U R I T Y marital satisfaction (Vannoy & Cubins, 2001), and showed how gender ideologies moderate the effects of wives' employment on marital stability and divorce (Greenstein, 1995;Kalmijn, De Graaf, & Poortman, 2004).…”
Section: The Moderating Role Of Gender Ideologymentioning
confidence: 97%
“…In the occupational domain, gender ideologies were found to be related to women's employment (Crompton & Harris, 1997), job attitudes (Gray, 1989a;Jones & McNamara, 1991), organizational commitment (Gray, 1989b) and career advancement (Gammie & Gammie, 1997). In the marital domain, studies have found associations between gender ideologies and J O B I N S E C U R I T Y marital satisfaction (Vannoy & Cubins, 2001), and showed how gender ideologies moderate the effects of wives' employment on marital stability and divorce (Greenstein, 1995;Kalmijn, De Graaf, & Poortman, 2004).…”
Section: The Moderating Role Of Gender Ideologymentioning
confidence: 97%
“…A body of literature also documents women's participation and experiences in the profession, the thrust being "to make visible inequality and work towards achieving equality between male and female accountants" (Gallhofer, 1998, p. 357). Within this, studies have suggested that women face continuing discrimination due to gender (Haynes, 2007a;Kirkham, 1997;Whiting and Wright, 2001) and/or race (McNicholas et al, 2004;Robinson-Backman and Weisenfeld, 2001); that there is a perception that child-rearing is a serious obstacle to women's promotion prospects (Barker and Monks, 1998;Gallhofer and McNicholas, 1998;Gammie and Gammie, 1997;Haynes, 2007b); that practices in audit firms reproduce gender domination (Anderson-Gough et al, 2005); or that gender is an important variable in explaining salary differentials in parts of the profession (Brennan and Nolan, 1998). However, a large proportion of research on gender and accounting relates to equality of opportunity and comparisons between men and women within the profession in the last decade, particularly in the US, using what Alvesson and Due Billing (1997) call "gender-as-a-variable" within research, or what might also commonly be referred to as "feminist empiricism" (Harding, 1987a).…”
Section: Current Gender and Accounting Researchmentioning
confidence: 99%
“…Our theory considers both person‐centred factors, such as assumed motivation and assumed attitudes, and situation‐centred factors, such as access to social networks (cf. Gammie & Gammie, 1997) and assumes that both these types of factors are infused with gender, with the effect of downplaying women's opportunities to pursue a fast career path in the industry. Thus, we base our theory on a gender perspective and implement it mainly by applying a social capital view.…”
Section: The Gendered Career Rein In the Auditor's Certification Processmentioning
confidence: 99%
“…Gendering and gendering processes seem to exist in most businesses. Several studies have investigated the determinants of success in pursuing a career as an auditor and why women are more or less absent in partnership positions (e.g., Anderson‐Gough et al ., 2005; Fogarty, 1996; Fogarty et al ., 1998; Gammie & Gammie, 1997; Lehman, 1990; Maupin, 1990, 1993; Whiting & Wright, 2001). Other studies have pointed out a larger tendency for women to plan to leave the business (Fogarty, 1996) in the middle of their careers; such departures might be a consequence ofthe fact that men appear to reach higher positions as managers, partners or underwriters earlier in their careers than women (Elg et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation